2023
DOI: 10.1007/s10340-023-01616-6
|View full text |Cite
|
Sign up to set email alerts
|

Attraction of Sitophilus oryzae (L.) (Coleoptera: Curculionidae) to the semiochemical volatiles of stored rice materials

Abstract: In order to explore the influence of stored cereal volatiles on the behavior of Sitophilus oryzae, the olfactory responses of adult rice weevils to the volatiles of different rice cultivars [Red brown rice (RBR), Daohuaxiangmi (DHXM), Baishuigongmi (BSGM), Yashuixinmi (YSXM), and white glutinous rice (WGR)] were studied using electroantennography (EAG) and behavioural bioassays in different types of olfactometers. S. oryzae showed significantly different preferences for these rice cultivars, in the order RBR &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…45 Cao et al reported that red brown rice volatiles hexanal and nonanal elicited significant EAG and behavioral responses at various concentrations to Sitophilus oryzae (Coleoptera: Curculionidae). 46 Ukeh et al showed that a synthetic blend of hexanal, octanal, and (E)-2-heptanal identified from maize seed volatiles was significantly attractive to Sitophilus zeamais (Coleoptera: Curculionidae). 47 Similar studies have been reported on various insect species, for example, Triatoma infestans (Hemiptera: Reduviidae), Dinoderus minutus (Coleoptera: Bostrichidae), and Apis cerana (Hymenoptera: Apidae).…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Cao et al reported that red brown rice volatiles hexanal and nonanal elicited significant EAG and behavioral responses at various concentrations to Sitophilus oryzae (Coleoptera: Curculionidae). 46 Ukeh et al showed that a synthetic blend of hexanal, octanal, and (E)-2-heptanal identified from maize seed volatiles was significantly attractive to Sitophilus zeamais (Coleoptera: Curculionidae). 47 Similar studies have been reported on various insect species, for example, Triatoma infestans (Hemiptera: Reduviidae), Dinoderus minutus (Coleoptera: Bostrichidae), and Apis cerana (Hymenoptera: Apidae).…”
Section: ■ Discussionmentioning
confidence: 99%
“…Heptanal, octanal, and nonanal are the main chemical component of cereal volatiles . Cao et al reported that red brown rice volatiles hexanal and nonanal elicited significant EAG and behavioral responses at various concentrations to Sitophilus oryzae (Coleoptera: Curculionidae) . Ukeh et al showed that a synthetic blend of hexanal, octanal, and (E)-2-heptanal identified from maize seed volatiles was significantly attractive to Sitophilus zeamais (Coleoptera: Curculionidae) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, sustainable control means as alternatives to chemical inputs during cereal storage are urgently needed 13 , 15 . Possible alternative control methods include the use of botanicals powders, extracts, and essential oils (EOs) of plant origin 13 , 16 23 , semiochemicals 12 , 14 , 24 , inert powder 25 31 and resistant varieties 32 .…”
Section: Introductionmentioning
confidence: 99%